Association of age and gender on prevalence of generalised attrition of mandibular molars - EVG, DR.KARTHIK; RANJAN, DR.MANISH; T.N., DR.UMA MAHESHWARI (The journal of contemporary issues in business and government, 2021)
Currently, Tooth wear is perceived internationally as the ever increasing problem, especially in the elderly as it is more prevalent in that age group.Further more, dietary habits, presence of GERD and socioeconomic status has also shown to affect the prevalence of tooth wear. The aim of the study is to check the association of age and gender on generalised attrition of lower molars.Tooth wear is used to describe the loss of hard tissue caused by frictional forces between opposing teeth or between the tooth's occlusal surface and food during masticatory and non-masticatory movements,with no occurrence of dental caries or trauma.The current study is an institutional based retrospective study performed over a review of 49832 cases. The results obtained shows the association of age and gender on prevalence of generalised attrition of lower molars. Within the limitations of the study, the most commonly affected gender is male and the most commonly affected age group with attrition is 25 to 84 years of age. The most commonly attrited lower molars is 36 followed by 46, 37 and 47 respectively.